IBRUTINIB IN THE MANAGEMENT OF NON-HODGKIN'S LYMPHOMA: A CASE REPORT - Durga Ts, Sree; K, Pavithran; Devi P, Uma (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Non-Hodgkin's lymphoma (NHL) is a diverse group of lymphoid neoplasms, the prevalence of which has increased over the past few decades. NHL is diverse in the manner of presentation, response to various treatment and prognosis. The current case report describes a 40-year-old man who was diagnosed with small lymphocytic lymphoma/chronic lymphocytic leukemia in 2006. The patient had disease progression during the course of 10 years from the time of diagnosis for which he received multiple lines of chemotherapy (chlorambucil/prednisolone; rituximab/cyclophosphamide/ fludarabine; bendamustine/rituximab; and ofatumumab). However, in 2016, his disease again showed signs of progression, and hence he was started on ibrutinib 140 mg 3 times daily. After treatment with ibrutinib, there were no clinical nodes and hepatosplenomegaly, and all counts also normalized. Since the commencement of this agent, no disease progression was observed for almost 16 months. However, in July 2017, again disease progression occurred, and the patient was started on with cyclophosphamide, vincristine, and prednisone (COP) regimen. He received one cycle of COP regimen and continued on treatment with ibrutinib, and the treatment was well tolerated. In December 2017, he expired due to the progression of the disease. Ibrutinib, a Bruton's tyrosine kinase inhibitor, appears to be safe and effective in providing long-term disease control even in refractory cases of NHL.